Teaching of second-degree equations in a competence framework: Enfoque didáctico y estudio exploratorio - Zarco García, Ana María; Lloréns Payá, Almudena (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This paper presents a review of the different approaches to teaching the second-grade equation for Secondary Education that are conjectured to be necessary to increase the quality of learning with the rigour and treatment required, highlighting the value of this topic itself and its applications. In addition, the results of an exploratory descriptive study accomplished on the knowledge of the second-grade equation of Secondary Education students are provided to finally draw the conclusion that their knowledge was not consolidated, and changes are needed.